A meta-analysis of mesophyll conductance to CO2 in relation to major abiotic stresses in poplar species. (19th March 2021) - Elferjani, Raed; Benomar, Lahcen; Momayyezi, Mina; Tognetti, Roberto; Niinemets, Ülo; Soolanayakanahally, Raju Y; Théroux-Rancourt, Guillaume; Tosens, Tiina; Ripullone, Francesco; Bilodeau-Gauthier, Simon; Lamhamedi, Mohammed S; Calfapietra, Carlo; et al.
Abstract: Mesophyll conductance ( g m ) determines the diffusion of CO2 from the substomatal cavities to the site of carboxylation in the chloroplasts and represents a critical component of the diffusive limitation of photosynthesis. In this study, we evaluated the average effect sizes of different environmental constraints on g m in Populus spp., a forest tree model. We collected raw data of 815 A–C i response curves from 26 datasets to estimate g m, using a single curve-fitting method to alleviate method-related bias. We performed a meta-analysis to assess the effects of different abiotic stresses on g m . We found a significant increase in g m from the bottom to the top of the canopy that was concomitant with the increase of maximum rate of carboxylation and light-saturated photosynthetic rate ( A max ). g m was positively associated with increases in soil moisture and nutrient availability, but was insensitive to increasing soil copper concentration and did not vary with atmospheric CO2 concentration. Our results showed that g m was strongly related to A max and to a lesser extent to stomatal conductance ( g s ). Moreover, a negative exponential relationship was obtained between g m and specific leaf area, which may be used to scale-up g m within the canopy. Abstract : Meta-analysis of mesophyll conductance in response to environmental constraints in Populus spp. showed significant effects of light gradient, soil moisture, and nitrogen but no response to copper and growth [CO2 ].